Embodied Protests : Emotions and Women's Health in Bolivia - Tapias, Maria (Book collections on Project MUSE., 2015)
'Embodied Protests' examines how Bolivia's hesitant courtship with globalization manifested in the visceral and emotional diseases that afflicted many Bolivian women. Drawing on case studies conducted among market- and working-class women in the provincial town of Punata, Maria Tapias examines how headaches and debilidad, so-called normal bouts of infant diarrhea, and the malaise oppressing whole communities were symptomatic of profound social suffering.